Evolution of IoT-enabled connectivity and applications in automotive industry: A review - Md. Abdur, Rahim; Rahman, Md. Arafatur; Rahman, M. M; Asyhari, A. Taufiq; Alam Bhuiyan, Md. Zakirul; Ramasamy, D. (Elsevier B.V., 2020)
Emerging Internet of Things (IoT) is considered as blessings for the automotive industry to offer vast opportunities to inventively create, develop, and enhance seamless services for the comfort of the users. Over time, IoT has significantly expanded and evolved in a numerous variety of automotive applications. Motivated by this growing importance of automotive IoT, this paper presents a critical literature survey on the utilization of IoT technology in the automotive industry, emphasizing the evolution of technology-enabling connectivity and applications. Initially, a review of the transformation and development of IoT-enabled smart systems for the vehicle is presented along with an extensive evaluation of the evolution of technology enabling IoT connectivity and applications. This then follows by the formulation of a comprehensive application scope of IoT technology and a general conceptual framework of IoT applications in the automotive industry. Detailed investigation of the benefits and challenges associated with deploying IoT applications is subsequently discussed together with proper identification of current and future technological challenges in the automotive industry. Furthermore, this study also focuses on assessing various connectivity types embedded in the sensor node functionalities and linked them with associated applications to reveal technical challenges for future automotive IoT advancement. This work is envisaged to shape the future perspectives of IoT technology in the automotive industry and impact the development of IoT platforms devised by the automotive industry-academia community. The promise of this technology will be realized through addressing new research challenges in the vehicular IoT paradigm, and the design of highly-efficient communication technology with minimum cost and efforts.